Nutrient contents in tempe produced from five cottage industries in Selangor, Malaysia - Wu, S. K.; Hasnah Haron (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study aimed to determine the nutrient contents in tempe produced by five cottage industries in Selangor, Malaysia. Proximate contents were analysed by using standard methods of AOAC (1997) while carbohydrate content was calculated by difference. Mineral contents, total dietary fiber (TDF), total phenolic content and total isoflavone content were determined by Atomic Absorption Spectrophotometry (AAS), enzymatic-gravimetric (AOAC 985.29), Folin-Ciocalteu colorimetric and High Performance Liquid Chromatography (HPLC) respectively. Macronutrients were reported in 100 g sample and the results showed the average nutrient contents were as follow: 63.07 ± 3.18% moisture, 19.63 ± 1.50% protein, 0.65 ± 0.17% fat, 0.70 ± 0.06% ash and 15.95 ± 1.88% total carbohydrate. The average mineral content in 100 g samples (based on wet basis) were 29.45 ± 5.67 mg calcium, 13.28 ± 5.76 mg magnesium, 3.48 ± 1.09 mg sodium and 2.06 ± 0.33 mg ferum. The results showed that the average of TDF content was 8.05 ± 3.65%. Total phenolic content was 259.87 ± 22.62 mg of GAE/g. The total isoflavone content in 100 g samples (wet basis) was 41.94 ± 10.42 mg/100 g. This study had shown that total phenolic content was significantly correlated (p < 0.01) with total isoflavone content in all tempe samples. It can be concluded that there was no significant difference (p > 0.05) in nutrient contents among tempe samples produced by five cottage industries located in Selangor, Malaysia. However, the mineral and isoflavone contents in the present study were lower compared to previous studies.